Efeito da inibição da NADPH oxidase sobre o estresse oxidativo e o fenótipo muscular esquelético de ratos com insuficiência cardíaca crônica induzida por estenose aórtica - Bonomo, Camila [UNESP] (2015)
Heart failure is characterized by a decreased functional capacity with early fatigue and dyspnea. Although intrinsic skeletal muscle changes may be at least partially responsible for these symptoms, mechanisms involved in muscle abnormalities are not completely clear. Myocardial and systemic oxidative stress is increased during heart failure. However, there is scarce information on the sources of oxygen reactive species (ROS) and on the role of oxidative stress in inducing skeletal muscle changes. NADPH oxidase complex is an important source of ROS; only a few studies have evaluated its activity in skeletal muscles during heart failure. In myocardial, apocynin can inhibit NADPH oxidase activity and reduce oxidative stress during cardiac injury. Purpose: In this study we evaluated the effects of the antioxidant apocynin on cardiac alterations and soleus muscle oxidative stress and phenotypic characteristics in rats with supravalvar aortic stenosis-induced heart failure. Methods: Twenty weeks after inducing aortic stenosis, Wistar rats were assigned into three groups: aortic stenosis (AS), AS treated with apocynin (AS-apo, 16 mg/kg/day dissolved in drinking water for eight weeks), and control (Sham). Transthoracic echocardiogram was performed before and after apocynin treatment. Activity of the antioxidant enzymes superoxide dismutase, gluthatione peroxidase, and catalase, and lipid hydroperoxide concentration were assessed by spectrophotometry in the soleus muscle. Serum concentration of malondialdehyde and soleus muscle NADPH oxidase activity and total ROS generation were analyzed by HPLC. Soleus myosin heavy chain composition was evaluated by electrophoresis and fiber cross-sectional areas were measured in hematoxylin and eosin-stained histological sections. Statistical analysis: one-way analysis of variance complemented by Bonferroni or Mann- Whitney test. Results: Before treatment, AS and AS-apo groups presented concentric hypertrophy ...